let y=x^2
12y^2 - 31y + 20 =0
(3y-4)(4y-5)=0
y = 4/3 or 5/4
x = sqrt(4/3) or sqrt(5/4)
2007-11-22 07:32:01
·
answer #1
·
answered by norman 7
·
0⤊
0⤋
This can be treated as a quadratic equation with x^2 as variable to begin with. Thus,
12x^4-31x^2+20=0
=> 12 (x^2)^2 - 31(x^2) + 20 = 0
=> 12 (x^2)^2 - 16(x^2) - 15(x^2) + 20 = 0
=> 4(x^2) (3x^2 - 4) - 5 (3x^2 - 4) = 0
=> (4x^2 - 5)(3x^2 - 4) = 0
=> 4x^2 = 5 or 3x^2 = 4
=> x = ± â5 / 2 or x = ± 2 / â3.
2007-11-22 15:35:14
·
answer #2
·
answered by Madhukar 7
·
0⤊
0⤋
Divide equation by x^2 giving:
12x^2-31x+20=0
(x-5/4)(x-4/3)=0
x=5/4 or x=4/3
2007-11-22 15:30:46
·
answer #3
·
answered by nivik 3
·
0⤊
0⤋
Notice you only have even powers. Replace your x^2 with, say, a y. Then your x^4 is the same as a y^2, right, so then you have:
12y^2-31y+20=0, which is a quadratic equation. Solve it for y as normal. Then, once you have those 2 solutions (if there are 2) notice that those are actually the answers for x^2, so you have to take the positive and negative square roots of those numbers to get your answers for x (there should be 4 answers).
2007-11-22 15:31:20
·
answer #4
·
answered by Chris S 2
·
0⤊
0⤋
I have no idea if this is right but this is how I would do it!! Good Luck!!
12x^4-31^2+20=0
=-19x^2+20=0
=-19x^2=-20
=19x^2=20
=x^2=20/19
=x= square root of 20/19
=1.0259
2007-11-22 15:38:05
·
answer #5
·
answered by xxSSxx 1
·
0⤊
0⤋
replace x² with u. then you have
12u² - 31u + 20 = 0
(3u - 4)(4u - 5) = 0
3u - 4 = 0
u = 4/3 = x²
x = â(4/3) = 2â(1/3) = (2/3)â3 .... or
4u - 5 = 0
u = 5/4 = x²
x = (1/2)â5
2007-11-22 15:32:44
·
answer #6
·
answered by Philo 7
·
0⤊
0⤋
I should know this...I'm half way through a maths degree at university.
I will edit if I remember...sorry.
2007-11-22 15:30:18
·
answer #7
·
answered by rosstopherz19 2
·
0⤊
0⤋